Chemosynthetic and photosynthetic trophic support from cold seeps in Arctic benthic communities - Åström, Emmelie K. L.; Bluhm, Bodil A.; Rasmussen, Tine L. (Frontiers in Marine Science, 2022)
Benthic communities below the photic zone are largely reliant on the export of surface-water primary production and the flux of partially degraded organic matter to the seabed, i.e. pelagic−benthic coupling. Over the past decades, however, the role of chemosynthetically produced carbon in food webs has been recognized in various habitats. Cold seeps are now known to be widespread across circumpolar Arctic shelves where natural release of hydrocarbons occurs at the seabed. Here, we investigated to what extent chemosynthesis-based carbon (CBC) enters the food web in a high latitude shelf-system. Specifically, we estimated the contributions of chemosynthesis-based carbon to primarily benthic invertebrate taxa from seeps at both shallow and deeper shelves and comparative non-seep areas in the Svalbard-Barents Sea region using bulk stable isotope-analysis of carbon and nitrogen. Our results show low δ13C values (-51.3 to -32.7 ‰) in chemosymbiotic siboglinids and several species of benthic, higher-trophic level, invertebrates (mainly polychaetes and echinoderms; -35.0 to -26.1‰) collected at cold seeps, consistent with assimilation of chemosynthesis-based carbon into the Arctic benthic food web. Using a two-component mixing equation, we demonstrate that certain species could derive more than 50% of their carbon from chemosynthesis-based carbon. These findings show that autochthonous chemosynthetic energy sources can contribute to supporting distinct groups of ‘background’ benthic taxa at these Arctic seep-habitats beyond microbial associations and chemosymbiotic species. Furthermore, we found a higher degree of chemosynthesis-based carbon in benthos at the deeper Barents Sea shelf seeps (>330 m) compared to seeps at the Western Svalbard shelf (<150 m water-depth), and we suggest this result reflects the differences in depth range, surface production and pelagic-benthic coupling. We detected large intra-species variations in carbon signatures within and across geographical locations and, combined with isotopic niche-analysis, our results show that certain taxa that inhabits seeps, have wider trophic niches in comparison to taxa inhabiting non-seeps. The increasing number of discovered natural seeps in the Arctic suggests that chemosynthetic production from seeps could play a more critical role in Arctic trophic structure than previously thought. Seep-derived carbon should, hence, be accounted for as an additional carbon source and included in food-web and energy-flow models in future work.